Chemical activation of the Piezo1 channel drives mesenchymal stem cell migration via inducing ATP release and activation of P2 receptor purinergic signaling. (21st January 2020) - Mousawi, Fatema; Peng, Hongsen; Li, Jing; Ponnambalam, Sreenivasan; Roger, Sébastien; Zhao, Hucheng; Yang, Xuebin; Jiang, Lin‐Hua
Abstract: In this study, we examined the Ca 2+ ‐permeable Piezo1 channel, a newly identified mechanosensing ion channel, in human dental pulp‐derived mesenchymal stem cells (MSCs) and hypothesized that activation of the Piezo1 channel regulates MSC migration via inducing ATP release and activation of the P2 receptor purinergic signaling. The Piezo1 mRNA and protein were readily detected in hDP‐MSCs from multiple donors and, consistently, brief exposure to Yoda1, the Piezo1 channel‐specific activator, elevated intracellular Ca 2+ concentration. Yoda1‐induced Ca 2+ response was inhibited by ruthenium red or GsMTx4, two Piezo1 channel inhibitors, and also by Piezo1‐specific siRNA. Brief exposure to Yoda1 also induced ATP release. Persistent exposure to Yoda1 stimulated MSC migration, which was suppressed by Piezo1‐specific siRNA, and also prevented by apyrase, an ATP scavenger, or PPADS, a P2 generic antagonist. Furthermore, stimulation of MSC migration induced by Yoda1 as well as ATP was suppressed by PF431396, a PYK2 kinase inhibitor, or U0126, an inhibitor of the mitogen‐activated protein kinase MEK/ERK signaling pathway. Collectively, these results suggest that activation of the Piezo1 channel stimulates MSC migration via inducing ATP release and subsequent activation of the P2 receptor purinergic signaling and downstream PYK2 and MEK/ERK signaling pathways, thus revealing novel insights into the molecular and signaling mechanisms regulating MSC migration. Such findings provide useful information for evolving a full understanding of MSC migration and homing and developing strategies to improve MSC‐based translational applications. Abstract : A, Exposure to Yoda1, the Piezo1 channel‐specific activator, stimulates human dental pulp mesenchymal stem cell migration in wound healing assay; B, the underlying signaling mechanisms.